Merzbau, the grave of the logocentric self: He who screams becomes the space - Pousada, Pedro (PORTO ARTE: Revista de Artes Visuais, 2016)
This article will discuss the Merzbau in Hannover as a "para-architecture" experience and as a doctrine on environmental comfort, connected to intense mnemonic feeling and relaxation. The Merzbau, the Gothic cubic "Traumhaus" (dream house) by Kurt Schwitters, is depicted here as a laboratory of sensory stimuli where an aesthetic control of oblivion, and of annoyance, has been practiced.